2017
DOI: 10.1155/2017/8715909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Regular Aerobic Activity in Young Healthy Athletes on Profile of Endothelial Function and Platelet Activity

Abstract: The aim of the study was to assess the impact of regular professional sports activity on the endothelial and platelet function in young men. The studied group were 79 young men (18–40 y, 25 athletes and 54 without any regular physical activity). The nitric oxide (NO) metabolic pathway intermediates, oxidative stress markers, mediators of inflammation, and platelet aggregation were measured. Flow mediated dilation (FMD) was studied before and after intravenous 16,0 g L-arginine infusion, which was repeated afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Several sources of evidence agree that acute aerobic exercise improves endothelial function [3]. In accordance with our findings, subjects on regular physical activity present improved endothelial function compared to physically inactive subjects [30], while the prospective follow up of subjects adopting an exercise training program confirms the beneficial effects on endothelial function [31]. Concerning the underlying mechanism implicated in the association of endothelial function with exercise, the production of nitric oxide (NO) by the endothelium is of great importance [32].…”
Section: Discussionsupporting
confidence: 91%
“…Several sources of evidence agree that acute aerobic exercise improves endothelial function [3]. In accordance with our findings, subjects on regular physical activity present improved endothelial function compared to physically inactive subjects [30], while the prospective follow up of subjects adopting an exercise training program confirms the beneficial effects on endothelial function [31]. Concerning the underlying mechanism implicated in the association of endothelial function with exercise, the production of nitric oxide (NO) by the endothelium is of great importance [32].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, ultrasound-derived β and Ep of the CCA were lower in ten young adult basketball players than in sedentary controls (Liu et al, 2015 ). In addition, higher flow-mediated dilation was observed in young adult athletes than in inactive controls (Podgorska et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, prolonged exposure to oxidative damage caused by physical exercise may result in several hormesis adaptations, such as activating antioxidative defense systems [87]. Podgorska et al [88] investigated the impact of aerobic training on athletes' endothelium profile and platelet function. Their findings indicated that no variations in the amounts of NO pathway metabolites existed.…”
Section: Exercise and Stress Oxidative In The Heartmentioning
confidence: 99%